PENGGUNAAN DESAIN AUDIT SEBAGAI PENGUKURAN AKTIVITAS DESAIN PADA UMKM KABUPATEN BANDUNG - Bijaksana Prabawa; Rahmiati Aulia; Ariesta Beta Nandya; Satria Eko Wicaksono (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
The Micro, Small, and Medium Enterprise (MSME) sector plays a strategic role in the economic growth of Indonesia. This is important because the majority of the Indonesian population has low education levels and relies on small businesses. One region in Indonesia with the most MSMEs is Bandung Regency with total of 476,954 business units. This has led to high business competition intensity in Bandung Regency. In order to compete, MSMEs require comparative advantages in a competitive business ecosystem. Based on previous research, design plays a significant role in shaping the competitiveness of established companies. However, the situation is different when design is implemented in micro scale business processes that have limitations. This research aims to determine the ability of MSMEs in Bandung Regency to apply design in their business processes. This study uses a mixed-method sequential explanatory approach, which combines quantitative and qualitative approaches. The research stages refer to the audit design framework through questionnaires, observations, and interviews to obtain a comprehensive analysis. The results of this study provide an overview of the issues faced by MSMEs and the extent of design utilization in their business processes. This research is expected to provide aesthetically pleasing and applicable design solutions for MSMEs. Keywords : design audit, design, Bandung Regency, MSMEs